1994
DOI: 10.1200/jco.1994.12.4.820
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the neurobehavioral functioning of patients before, during, and after bone marrow transplantation.

Abstract: Pretransplant emotional and cognitive functioning are important determinants of long-term outcome and quality of life (QOL) in BMT patients. In addition, a few patients undergoing BMT develop short-term memory difficulties and mood disturbance that may persist. Pretransplant identification of patients at risk for neurobehavioral difficulties may guide early interventions during hospitalization. Posttransplant assessment may then be used to develop rehabilitation programs and other interventions for individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
111
3
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 18 publications
4
111
3
1
Order By: Relevance
“…These results are notable because these problems remain largely underdiagnosed, 41,55,56 and most would be expected to be exacerbated rather than diminished with the beginning of aggressive high-dose therapy and transplant regimens. 27,28,33 The prevalence rates found in the present investigation are even higher than those that emerged in our earlier pilot study of myeloma patients at a similar point in treatment; 24 taken together, these studies demonstrate that early psychosocial screening is feasible in a busy treatment center and that supportive care needs are extensive. On the SF-12, for example, 59% of patients in the current study exceeded cutoffs (1 s.d.)…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…These results are notable because these problems remain largely underdiagnosed, 41,55,56 and most would be expected to be exacerbated rather than diminished with the beginning of aggressive high-dose therapy and transplant regimens. 27,28,33 The prevalence rates found in the present investigation are even higher than those that emerged in our earlier pilot study of myeloma patients at a similar point in treatment; 24 taken together, these studies demonstrate that early psychosocial screening is feasible in a busy treatment center and that supportive care needs are extensive. On the SF-12, for example, 59% of patients in the current study exceeded cutoffs (1 s.d.)…”
Section: Discussioncontrasting
confidence: 51%
“…[26][27][28][29] Rates of distress have been similarly elevated among more heterogeneous samples of patients assessed prior to receiving either autologous, allogeneic, or matched unrelated donor transplants. [30][31][32][33] Many patients also appear to experience compromised physical or functional status prior to autologous transplantation, although here too information is limited. 28,34,35 Most studies that evaluated patients prior to autologous PBSCT have relied on small sample sizes and, as noted, individuals with multiple myeloma were rarely included, in part due to exclusion of older patients from transplant regimens.…”
mentioning
confidence: 99%
“…26,39,40 The prospective design shows a slight decline in anxiety in the SCT group and relatively stable levels (ASCT group) during hospitalization and follow-up, and an increase in depression during hospitalization before it consistently declined in both groups. This pattern of change was in line with two prospective studies employing the State Trait Anxiety Inventory (STAI) and the Zung Depression Inventory, 41 and the POMS, 6 but contradicted slightly with other studies reporting minor changes in psychological distress during follow-up assessed by the POMS 5 and Beck's Depression Inventory (BDI). 4 The level of psychological distress in the transplant patients was generally lower in this report compared with other studies employing the HADS scale.…”
Section: Discussionmentioning
confidence: 49%
“…The multivariate approach in this subgroup of patients showed that higher baseline scores were the strongest predictive factors for more anxiety and depression at subsequent assessments, as well as for anxiety cases after 1 year, as reported by other. 23,41 Treatment with ASCT was associated with more anxiety after 1 year. A less favourable outcome in the ASCT group than in the SCT groups, is in line with our previous report of health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…They reported memory deficits and reduced information-processing speed in particular. Meyers et al 33 reported signs of mild cognitive deficits in 20% of their subjects before HSCT. Andrykowski et al 34 reported similar findings.…”
Section: Introductionmentioning
confidence: 99%